Exploring the participation and agency of students with special education needs in a Macau-Chinese secondary school - Correia, Ana M.; Forlin, Chris; Sio, Eva (Journal of Research in Special Educational Needs, 2022)
The research explores the perceptions of five secondary school students with special education needs (SEN) about their participation in learning, group membership, and agency within an inclusive school in Macau SAR. This goal is achieved by using students' voices documented in open-ended interviews and is underpinned by the conceptual framework of heutagogy. The aim is to shed light on students' perceptions on school effectiveness in supporting their needs through successful participation and agentic possibilities. Findings showed that students were more prone to social rejection and being isolated or bullied than their peers. They were struggling to feel included or participate, their needs were only partially being met, and they had few opportunities to exert influence on their educational trajectories. Recommendations are provided to assist educators and schools in enhancing students with SEN to connect to the learning process and community, with the provision of appropriate learning adjustments and more active approaches to ensure their acceptance by mainstream students, including the formation of coaching peers to assist in developing social and academic skills under teacher's scaffolding practices. This study highlights the contribution of the heutagogical perspective to advance research on the participation and agency of students with SEN in mainstream schools.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1471-3802.12566
Keywords: Macau SAR; Special education needs; agency; disability; inclusive education; participation; students' voice

Enhancing Teacher Education by Utilizing a Revised PGDE Curriculum as a Fundamental Resource for Inclusive Practices in Macao - Monteiro, Elisa; Forlin, Chris (International Perspectives on Inclusive Education, 2021)
Keywords: Inclusive education; Knowledge transfer; Pedagogical practice; Post-graduate diploma in education; Programme design; Teachers

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.
1 citations (Crossref) [2022-09-21]

Validating the use of the 24-item long version and the 12-item short version of the Teachers’ Sense of Efficacy Scale (TSES) for measuring teachers’ self-efficacy in Macao (SAR) for inclusive education - Monteiro, Elisa; Forlin, Chris (Emerald Open Research, 2020)
Validation of the Teachers’ Sense of Efficacy Scale (TSES) for use with teachers in Macao (SAR) was undertaken to determine its usefulness as a measure of teacher self-efficacy for inclusive education. This paper discusses the results found by analyzing various versions of the TSES and TSES-C in a Chinese format with 200 pre-service teachers in Macao (SAR).  Psychometric analyses were undertaken to investigate the validity of the existing scales and the three and two factor solutions. The results indicated a preferred 9-item version that produced improved factor loadings and reliabilities. The use of a relatively quick and short scale to measure such a complex phenomenon as teacher self-efficacy is discussed. Issues are raised regarding generalizability of scales and the impact of culture, demographics, and edifying issues that may impact on the usefulness of such scales.
Type: article
Keywords: Inclusive education; Macao; scale development; self-efficacy

Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education - Monteiro, Elisa; Kuok, A. C. H.; Correia, Ana; Forlin, Chris; Teixeira, Vitor (International Journal of Inclusive Education, 2019)
This paper reports findings of a mixed methods study examining private school teachers’ perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.
9 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2018.1514762
Keywords: Inclusive education; Macao; teacher education; teacher efficacy

Placement, inclusion, law and teachers’ perceptions in Macao’s schools - Teixeira, Vitor; Correia, Ana; Monteiro, Elisa; Kuok, A. C. H.; Forlin, Chris (International Journal of Inclusive Education, 2018)
In Macao, the government has initiated a debate regarding revisions in the Decree Law in order to promote a more inclusive schooling system. In this Special Administrative Region of China, inclusive education is one of three possible types of special education that are likely be legislated in the future. The way the teachers perceive the different aspects related to inclusive education, namely the principles, concepts and law, is essential for its full implementation. The aim of this study is to understand teachers’ perceptions about the proposed amendments in the consultation document for changes in the special education regime. In particular, we focus on teachers’ acceptance of the recommended role of parents, the proposed placement models and expectations for teacher training. A mixed-methods approach with a survey of a sample of 500 teachers in private schools and interviews to a sub-sample of 20 provide the data. While agreeing in principle with the majority of the proposed changes in the Decree Law, there were several reservations made by the teachers, especially regarding the extent of parental choice, placement decisions and teacher training. Recommendations to continue the pathway for a more inclusive education system in Macao and for further research are made.
7 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13603116.2017.1414318
Keywords: Disability; education policy; inclusive education; special education; special education needs